Analisis Resepsi Khalayak Pada Aplikasi Peduli Lindungi Di Masa Pandemi COVID 19 - Dittya Ayu; Solten Rajagukguk (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2022)
Peduli Lindungi application is a policy issued by the Government that must be owned by all Indonesian people. This study uses Stuart Hall's reception analysis theory which focuses on individual acceptance and response to media messages. This study uses a qualitative method using a constructivist paradigm and is descriptive. Data collection was carried out using in-depth interviews with a number of seven informants who are audiences who use and know the Care Protect Application and have different backgrounds. After analyzing the results of the research, it can be concluded that the reception of the informants towards the Care to Protect Application is in the Negotiation position. Where many of the informants gave a generally positive view, but there were some suggestions, to develop Peduli Lindungi Applications.